الإدارة البيئية في المنشآت الصغيرة والمتوسطة حالة دراسية في مدينة حلب القديمة - معن الشبلي (Tishreen University, 2019)
The City of Aleppo, with its two millions inhabitants, is considered a metropolis for the northern regions of Syria and a central point making it the first economic city in Syria. Small and medium enterprises have an important role to play in the economies of developing countries both in terms of job creation and its percentage of the Gross National Products. Traditional Small and medium sized companies are basically located in the Old City boundaries, they play an important role under quantitative and qualitative aspects by providing some 25000 jobs. They cohabit side by side with trade, services, industries and housing which lead to an uneven high pressure on the environment. In fact, degraded environment means, on the long term, the reduction of the quality of life, reduction of people healt etandards and the relocation of important economic activities especially tourism from which these traditional companies could take the maximum advantage of attracting tourists. From this point of view, improving the SMEs environmental performance and management is considered a step towards better environment and sustainable development in the Old City. It will help to build experience in the field of SME and to  enhance the cooperation between the Municipality and the private sector in order to promote the idea of the Public-Private-Partnership; it will also provide an orientation on how to manage the SMEs, and produce guidelines for urban SME environemtnal management to be disseminated either to further SME promotion in Aleppo or to other interested Municipalities in Syria. With the cooperation of the Municipality of Aleppo, we will try to provide a sustainable and enhanced environmetal and economic bases for the inhabitants to stay in the Old City of Aleppo, which controls the out-migration and prevents the dilapidation of its historic World Heritage core.   تعتبر مدينة حلب, التي يبلغ عدد سكانها مليوني نسمة, عاصمة للمناطق السورية الشمالية إضافة إلى كونها مركز جذب هام مما أدى إلى اعتبارها المدينة الاقتصادية الأولى في سورية. إن الشركات الصغيرة والمتوسطة لها دور متنام وهام لتلعبه في تنمية الاقتصاد في الدول النامية نظراً لفرص العمل التي تساعد على خلقها ولنسبة مساهمتها في الناتج القومي.  تتوضع هذه الشركات بشكل أساسي ضمن حدود المدينة القديمة فهي نلعب دوراً مهماً من الناحيتين الكمية والكيفية لأنها تؤمن 25000 فرصة عمل, وهي تتواجد جنباً إلى جنب مع التجارة والخدمات الصناعية والسكن, وهذا كله يؤدي إلى ضغط بيئي عالٍ وغير متوازن. في الحقيقة, إن الانحدار البيئي يعني, وعلى المدى البعيد, التقليل من المستوى المعيشي والتأثير على صحة السكان ونقل بعض النشاطات الاقتصادية الهامة وخاصة السياحة والتي بإمكان هذه الشركات التقليدية أن تستمد منها الفائدة القصوى عن طريق جذب السياح. ومن هذا المنطلق, فإن تحسين الأداء والإدارة البيئية للمؤسسات التجارية الصغيرة والمتوسطة يعد خطوة هامة لتقديم بيئة أفضل وتنمية مستدامة في المدينة القديمة. كما أنه سيساعد على بناء خبرة في مجال المؤسسات التجارية الصغيرة والمتوسطة, بالإضافة إلى تعزيز التعاون بين مجلس المدينة والقطاع الخاص من أجل تطوير فكرة المشاركة بين القطاع الخاص والقطاع العام, وإنتاج خطوط توجيهية حول الإدارة البيئية المؤسسات التجارية الصغيرة والمتوسطة لكي يتم نشرها إما من أجل تطوير مستقبلي للمؤسسات التجارية الصغيرة والمتوسطة الحجم في مدينة حلب أو لمجالس مدن أخرى مهتمة بهذا الموضوع في سورية. بالتعاون مع مجلس مدينة حلب, ستتم المحاولة لتقديم قواعد أفضل استدامة بيئياً واقتصادياً من أجل السكان وذلك لضمان بقائهم ضمن مدينة حلب القديمة وذلك سوف يقلل من الهجرة خارج المدينة القديمة ويمنع من تخريب جوهرها التاريخي كموقع اثري عالمي.